Exploring translation theories - Pym, Anthony (Routledge, 2014)
Includes bibliographical references and index; What is a translation theory? -- Natural equivalence -- Directional equivalence -- Purposes -- Descriptions -- Uncertainty -- Localization -- Cultural translation